2020
DOI: 10.1111/odi.13363
|View full text |Cite
|
Sign up to set email alerts
|

World Workshop on Oral Medicine VII: Prognostic biomarkers in oral leukoplakia and proliferative verrucous leukoplakia—A systematic review of retrospective studies

Abstract: Objective To systematically review retrospective studies examining prognostic potentials of candidate biomarkers to stratify malignant progression of oral leukoplakia (OL) and proliferative verrucous leukoplakia (PVL). Materials and Methods A systematic literature search of PubMed, EMBASE, Evidence‐Based Medicine and Web of Science databases targeted literature published through 29 March 2018. Inter‐rater agreement was ascertained during title, abstract and full‐text reviews. Eligibility evaluation and data ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 74 publications
0
26
0
2
Order By: Relevance
“…The two recent WWOM systematic reviews on oral leukoplakia identified insufficient evidence to support validated prognostic biomarkers for stratification and long‐term surveillance of OLK and PVL progressing to cancer (Celentano et al., 2020; Villa, Celentano, et al, 2019). This is not surprising given that both reviews utilised very strict inclusion criteria for clinical, histopathological and follow‐up characteristics of all included leukoplakia cases.…”
Section: Molecular Determinants Of Progression To Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The two recent WWOM systematic reviews on oral leukoplakia identified insufficient evidence to support validated prognostic biomarkers for stratification and long‐term surveillance of OLK and PVL progressing to cancer (Celentano et al., 2020; Villa, Celentano, et al, 2019). This is not surprising given that both reviews utilised very strict inclusion criteria for clinical, histopathological and follow‐up characteristics of all included leukoplakia cases.…”
Section: Molecular Determinants Of Progression To Cancermentioning
confidence: 99%
“…Recently, two systematic reviews undertaken by members of the Precision Medicine Work Group of the World Workshop on Oral Medicine (WWOM) VII (Celentano, Glurich, Borgnakke, & Farah, 2020; Villa, Celentano, et al, 2019) identified insufficient longitudinal prospective evidence to support validated prognostic biomarkers for OLK (Villa, Celentano, et al, 2019) and no evidence to support translation of candidate biomarkers predictive of malignant transformation of OLK and PVL in retrospective studies (Celentano et al., 2020). Both papers noted the need for additional research into the genomic and molecular profiles of both disorders, specifically calling for systematically designed, large, optimally controlled, collaborative, prospective and longitudinal studies with a priori‐specified methods to identify, recruit, prospectively follow and test for malignant transformation to enhance feasibility of prognostic biomarkers predicting cancer progression of OLK and PVL (Celentano et al., 2020; Villa, Celentano, et al, 2019). As powerful as these systematic reviews and their resultant conclusions are, their clinical applicability is constrained by the stringency of their inherent design, execution and reporting.…”
Section: Introductionmentioning
confidence: 99%
“…2 The lack of highly specific and sensitive, validated clinical, histopathological or molecular biomarkers to predict the MT of OPMDs has contributed to the high mortality and morbidity rates of OSCC. 3 OED alone does not inevitably indicate progression to malignancy, simultaneously; the absence of dysplastic features does not necessarily preclude the likelihood of the MT. 1,4 In addition to being invasive and associated with high morbidity, the accurate diagnosis by incisional biopsy requires correct site selection, which often relies on an experienced clinician or specialist.…”
Section: Introductionmentioning
confidence: 99%
“…Un particolare tipo di leucoplachia viene definitiva leucoplachia verrucosa proliferativa (LPV) che è caratterizzata da una progressiva diffusione di lesioni intra-orali multifocali che possono estendersi fino a coinvolgere la gran parte delle mucose orali (Figura 7) (50,51).…”
Section: Leucoplachia Ed Eritroplachiaunclassified